2020
DOI: 10.1111/jfpe.13484
|View full text |Cite
|
Sign up to set email alerts
|

Design and performance evaluation of a passive flat plate collector solar dryer for agricultural products

Abstract: A passive flat plate collector solar dryer (FPC-SD) was designed and fabricated for drying of agricultural products. It has drying capacity of 7.5 kg, drying chamber cross sectional area of 0.74 m × 0.58 m, collector aspect ratio 2, collector depth of 0.25 m and hence volume of 0.5 m 3. Total pressure drop across drying bed ΔP T was 1.29 kg/m 2. The difference between the dryer inlet and ambient temperature was recorded for certain days and was 24.6 C at 1.30 p.m. with average solar insolation of 882.35 W/m 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…Cleaned leaves were subjected to three different drying methods‐ solar drying, tray drying and microwave drying. Solar drying was carried out in an indirect type natural convection solar dryer developed and installed at the National Institute of Food Technology Entrepreneurship and Management (NIFTEM) under the Ministry of Food Processing Industries, Government of India (Babar et al., 2020). Solar drying was carried out under cross flow air pattern.…”
Section: Methodsmentioning
confidence: 99%
“…Cleaned leaves were subjected to three different drying methods‐ solar drying, tray drying and microwave drying. Solar drying was carried out in an indirect type natural convection solar dryer developed and installed at the National Institute of Food Technology Entrepreneurship and Management (NIFTEM) under the Ministry of Food Processing Industries, Government of India (Babar et al., 2020). Solar drying was carried out under cross flow air pattern.…”
Section: Methodsmentioning
confidence: 99%
“…Also, the average activation energy was found to be 36.39 kJ/mol for the dried mushroom. Babar, Tarafdar, Malakar, Arora, and Nema (2020) designed and fabricated an indirect type solar dryer with an energy storage device for drying button mushroom. It was observed that the equilibrium moisture content achieved by the dried mushroom in 33 hr and 21 hr for open sun drying and indirect type solar dryer, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Babar, Tarafdar, Malakar, Arora, & Nema [32] designed a passive flat plate collector (FPC) with phase change material. The dryer was used to dry button mushroom, and its performance was compared to open sun drying.…”
Section: Passive Solar Dyermentioning
confidence: 99%